KAJIAN EKONOMI PROGRAM BANK SAMPAH DI MAKASSAR (Study on Economic Benefit of Garbage Bank Program in Makassar) - Musran Munizu; Sumardi Sumardi; Imran Tajuddin (Jurnal Inovasi dan Pelayanan Publik Makassar, 2017)
Garbage bank is established as a place to foster, train, assist, buy and market the results of waste management activities from the community. Garbage bank is a form of a local community initiative in efforts to solve community-based waste issues. Garbage banks are expected to provide high economic benefits for improving community welfare. The population of this study is all customers of garbage bank in Makassar as many as 40,114 people. The number of samples as many as 105 respondents. Both descriptive statistical analysis and SWOT analysis was used as the method of analysis. Then, in-depth interviews with stakeholders that consists of government, academic, private, NGO, and community leaders in formulating strategy and policy to develop of garbage bank program in the future. The results of the study indicate that generally the community associated with the garbage bank comes from the socio-economic group with the middle to lower class. The level of knowledge and community participation is still relatively low on waste management and 3R (reduce, reuse and recycle) principles in waste segregation. The garbage bank program brings blessings and economic benefits to society. Beside as a source of additional income for the community, garbage banks can also encourage changes in people's behavior to live healthy and clean, care for the environment and other socio-economic benefits. Furthermore, development strategy of garbage bank should be directed to innovative and strategic programs that can increase the interest of the community to participate actively as the participants/customers of garbage banks. Then, commitment and synergy between regional government and stakeholders is a key factor in improving both economic benefits and development of garbage bank programs in the future.